Frequency of Miscarriage in Newly Married Females Due to Teratogenic Drugs i.e. Selective Serotonin Reuptake Inhibitors and Anti-Epileptics - Kaleemullah, Hafiz; Jahanzeb,; Abdul Raheem,; Asad Ullah,; Sanaullah,; Asmat , Fauzia (Indus Journal of Bioscience Research, 2025)
Background: Miscarriage is still a major reproductive health issue, particularly in areas where access to specialized treatment is scarce. In particular, newlywed women who might not be aware of the dangers of pharmaceuticals like selective serotonin reuptake inhibitors (SSRIs) and antiepileptic drugs (AEDs) may be at risk for teratogenic drug exposure during the early stages of pregnancy. Objective: The purpose of this study is to determine the rate of miscarriages among newlywed women in Quetta who were exposed to SSRIs and AEDs during the early stages of pregnancy. Methods: One hundred and twenty pregnant women in their first trimester who were enrolled at a tertiary care hospital participated in this qualitative study. The participants' exposure to antiepileptic medications (AEDs) or SSRIs was evaluated. With an emphasis on fetal outcomes, data were gathered via medical records and structured interviews. Prior to starting the data collection process, ethical permission was acquired. Results: Thirty-five (29.2%) of the 120 participants were exposed to SSRIs, twenty-five (20.8%) to AEDs, and sixty (50%) did not. Five (20%) of the AED group had fetal abnormalities, compared to six (17.1%) of SSRI users. There were just two (3.3%) abnormalities in the group that were not exposed, suggesting that medication exposure increases risk. Conclusion: An increased risk of miscarriages was linked to early prenatal exposure to SSRIs and AEDs. Insufficient counselling emphasizes the necessity of increased knowledge and prenatal preparation to reduce drug-related hazards and enhance results for both the mother and the fetus.